STUDI EKSPERIMENTAL BETON ADUKAN KERING DENGAN MENGGUNAKAN METODE PIPA BERKATUP PADA AIR GAMBUT - Sulung, Odie; ., Herwani; Supriyadi, Asep (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2015)
The development of increasingly advanced technology in all fields, including the field of construction. be it residential, office buildings, bridges, highways, dams, ports and so on. Effect of water level at the time of casting, often become problems and obstacles for planners in determining the characteristics of the concrete to be used in the construction. Investigators therefore conducted research to test specimens of concrete with compressive strength of concrete dried mortarusing peat water with the method of casting pipe with valves, where in the mold (cylinder) there are puddles of peat 50% of the mold, with a view to determine the compressive strength of concrete driedmortarand influence on the amount of peat puddles on the formwork (cylinder). In the manufacture of test specimens using ACI method of normal concrete with plan compressive strength of 25 MPa. Where cement, fine and coarse aggregates mixed with the water needs of normal concrete mix design. Casting method is done by pouring concrete into a mold to dry mixture contained 50% of the puddle prints.Â 15 cm, height 30 cm. Diamater Test objects are made cylindrical withÂ Testing / testing includes testing the compressive strength and modulus of elasticity test. As a comparison is made also samples of normal concrete and concrete dry peat water with direct pour pipe methods. From the research value of the concrete compressive strength of the dried mortar using peat water with a variable water level of 50% obtained average value of compressive strength characteristics - average 25 MPa for normal concrete, 11.06 MPa for dried concrete peat valves and 8.85 MPafor dry concrete without valve , Water uptake value per sample average is 16,5 %for dry concrete with pipes valves and 15,54 % for methods pipe without valve. Cement loses value the average per sample is 29% to methods of pipe valves and 31% for pipes without valves. Pattern collapse of the specimen on the waterlogged peat areas due to the binding material that is not perfect. Keywords: the amount of peat puddles, compressive strength, concrete mortar dry